Morphological evolution caused by many subtle-effect substitutions in regulatory DNA - Frankel, Nicolás; Erezyilmaz, Deniz F.; McGregor, Alistair P.; Wang, Shu; Payre, François; Stern, David L. (Nature (London), 2011)
Morphology evolves often through changes in developmental genes, but the causal mutations, and their effects, remain largely unknown. The evolution of naked cuticle on larvae of Drosophila sechellia resulted from changes in five transcriptional enhancers of shavenbaby ( svb ), a transcript of the ovo locus that encodes a transcription factor that governs morphogenesis of microtrichiae, hereafter called ‘trichomes’. Here we show that the function of one of these enhancers evolved through multiple single-nucleotide substitutions that altered both the timing and level of svb expression. The consequences of these nucleotide substitutions on larval morphology were quantified with a novel functional assay. We found that each substitution had a relatively small phenotypic effect, and that many nucleotide changes account for this large morphological difference. In addition, we observed that the substitutions had non-additive effects. These data provide unprecedented resolution of the phenotypic effects of substitutions and show how individual nucleotide changes in a transcriptional enhancer have caused morphological evolution. Step-by-step evolutionary change Morphological evolution often involves changes in developmental genes, but the number and effects of the causal mutations remain largely unknown. Frankel et al . use the gene shavenbaby in Drosophila sechellia as a model system for studying the genetics of this phenomenon. They show that evolutionary change in one of the five cis -regulatory enhancers of shavenbaby resulted from many nucleotide substitutions that altered both the timing and level of gene expression. Thus many mutations of small effect — not just one mutation of large effect — were needed for this fruitfly to evolve a hairless larva. The work provides quantitative support, at the single nucleotide substitution level, for Charles Darwin's favoured view of a 'gradualist' evolutionary process.